Analysis of an optimal public transport structure under a carbon emission constraint: a case study in Shanghai, China - Zhang, Linling; Long, Ruyin; Chen, Hong; Yang, Tong (Environmental science and pollution research international, 2018)
Along with the rapid development of the transportation industry, the problems of the energy crisis and transport emissions have become increasingly serious. The success of traffic emission reduction is related to the realization of global low-carbon goals. Placing priority on public transport is the internationally recognized traffic development model. This paper takes Shanghai, China, as an example to examine the optimal public transport structure. Five factors were selected from personal and public perspectives, including travel costs, crowding degree, occupied area, traffic emissions, and operating subsidies. The objective functions of these factors were transformed into satisfaction functions, and a multi-objective programming model was used to solve for the optimal proportions of the ground bus and rail transit, and the carbon emission reduction potential was analyzed in different scenarios. The study showed that the actual proportion of rail transit in Shanghai was slightly lower than the optimal value, and accompanied by low satisfaction with each factor relative to the optimal value. It was difficult to achieve the traffic emission reduction targets by only reducing satisfaction with other factors except carbon emissions assuming a fixed proportion of public transport. As the proportion of total travel represented by public transport increased, rail transit became the main mode of public transport and the usage trend was more obvious, but the structure of public transport gradually reached a relatively stable state after a certain level of development. Compared to reducing carbon emissions by changing satisfaction with other factors, it was easier to achieve traffic emission reduction targets by increasing the proportion of public transport. To increase the proportion of public transport travel and achieve the goal of traffic reduction in the future, further improvements are needed in the quality of public transport system services, public transport priority development must be differentiated, and the profitability of the public transport industry itself must be enhanced.